PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR SISWA SMP - Atriana Lopsau; St. Muthmainnah Yusuf; Uke Ralmugiz (MEGA: Jurnal Pendidikan Matematika, 2022)
This study aims to develop mathematical learning media with the Discovery Learning model on valid, practical and effective junior high school students' learning outcomes. This research is a Research and Development (R&D) study. The product developed ar learning media in the form of lesson plans and worksheets using the Discovery Learning model on students' mathematics learning outcomes. The R&D research design used in this study is ADDIE which consists of 5 stages, namely: Analyze, Design, Development, Implement, and Evaluate. The data collection instruments are Validation Sheet, Student Response Questionnaire and Concept Understanding Test Sheet. The data analysis techniques for the development of each learning media were in valid, practical and effective criteria. The study showed that, in terms of validity, the average of validation learning media was 3.65 with valid criteria. In terms of practicality, based on practicality trials, it was found that the results of the students’ response questionnaire to the learning media reached an average of 88.75% and was considered practical so that it was feasible to use. As for the results of the completeness level of the effectiveness analysis reached 80% with very effective criteria. Based on the above, it can be concluded that the development of learning media with discovery learning learning models on mathematics learning outcomes for junior High school of Muhammadiyah Kupang students was valid, practical and effective and can be used in learning.